INNOVATION OF PROCESSING RICE INTO FLOUR BY USING A PORTABLE MILLING MACHINE - Haki, Ubay; Sanifah, Sanifah; Idris, Idris; Aziz, Abdul (Nindikayla Institute, 2024)
The purpose of the KKM-Thematic program is that students can analyze problems and focus on mentoring to prepare superior human resources based on the Creative Economy. The problem in the community of Cerukcuk Village is the lack of skills in processing rice into other processed. The method of implementation in this devotion is (1) identifying the problems in Cerukcuk Village, (2) making Portable rice flour milling machines, (3) testing the use of Portable rice flour milling machines, (4) evaluation, (5) socialization to the community. The result of this activity is that the community can make Portable rice flour milling machines and can use it themselves to improve the economy of the community of Cerukcuk Village.